Antioxidant and Ultrastructural Alterations in Wheat During Drought-Induced Leaf Senescence - Turana Y. Isgandarova; Samira M. Rustamova; Durna R. Aliyeva; Fuad H. Rzayev; Eldar K. Gasimov; Irada M. Huseynova (Agronomy)
Wheat is one of the most important crops to ensure food production globally. Understanding the mechanism of leaf senescence in wheat plays a crucial role in improving its productivity and resilience under various stress scenarios. In this study, we investigated biochemical, functional, and ultrastructural changes during leaf senescence in wheat genotypes with contrasting drought tolerance. For this, key parameters such as chlorophyll and total protein content, membrane stability, malondialdehyde level, and the activity of antioxidant enzymes (superoxide dismutase, ascorbate peroxidase, guaiacol peroxidase, benzidine peroxidase, and catalase) were comparatively analyzed during both natural and drought-induced senescence. Additionally, the expression of superoxide dismutase isoform genes functioning in different cellular compartments was studied, alongside ultrastructural changes in flag leaves. The experiments involved genotypes of bread wheat (Triticum aestivum L.) and durum (Triticum durum Desf.) wheat. The plants were grown in controlled environment chambers under control and drought conditions using a completely randomized design. After the booting stage, irrigation was discontinued for drought-treated plants. Flag leaves were sampled at 7, 14, 21, 28, and 35 days after anthesis. Drought-tolerant genotypes exhibited slower chlorophyll degradation, lower lipid peroxidation, enhanced membrane stability, and stronger antioxidant responses, allowing them to maintain cellular function longer, whereas sensitive genotypes showed accelerated leaf senescence. Transcript levels of FeSOD increased significantly post-flowering but declined as senescence progressed, while MnSOD expression exhibited a rise towards the later stages of ontogenesis across all studied genotypes. Ultrastructural analysis revealed progressive damage to chloroplast membranes, thylakoid structures, and mesophyll cell walls under stress conditions, particularly in sensitive genotypes. These findings contribute to a deeper understanding of the physiological and molecular responses of wheat to drought stress, offering potential targets for improving crop performance in water-limited environments.